Synthesis and characterization of NaNbO3 mesostructure by a microwave-assisted hydrothermal method - Teixeira, Guilhermina Ferreira [UNESP]; Zaghete, Maria Aparecida [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Springer Nature, 2014)
In the present work, we report the synthesis and characterization of NaNbO3 particles obtained by microwave-assisted hydrothermal method from Nb2O5 and NaOH. The synthesis was made at different periods at 180 °C and 300W. The crystallization of NaNbO3 structures produced Na2Nb2O6.H2O in the intermediate phase with fiber-like morphology, and this is associated with the synthesis time. Pure orthorhombic NaNbO3 with cube-like morphology originates after synthesizing for 240 minutes. To verify the remnant polarization of particles, films were obtained by electrophoresis process and sintered at 800°C for 10 minutes in a microwave furnace. The films characterization indicated that films of niobate with fiber-like morphology present remaining polarization, and the morphology of cubes did not show remaining polarization. Considering these results, it can be concluded that the morphology implemented ferroelectric property of NaNbO3.